Study of Thyroid Function in Adolescent Girls with Intellectual Disabilities - Arun Joshi, Ganesh; Ganesh Joshi, Prajakta (International Journal of Medical Research and Review, 2014)
Introduction: Thyroxine is an important hormone that ensures proper growth and development throughout life. It has an important role in the development of the reproductive system. Methods: The objective of this study was to evaluate the thyroid status of adolescent girls with disabilities. A survey was undertaken at a residential institution on all adolescent girls with disabilities in 10-19 years age group. There were 21 girls with intellectual disabilities. Their sexual development was noted. Thyroid profile was advised in all subjects. Results: There were 2 girls who had not developed any secondary sexual characters but they showed normal thyroid profile. The thyroid profile was deranged in 1 girl who had Down’s syndrome and another girl had subclinical hypothyroidism. Conclusion: The study concludes that thyroid profile should be done at regular intervals in adolescent girls with intellectual disabilities, especially Down’s syndrome.